Tomographic Aspects of Advanced Active Pulmonary Tuberculosis and Evaluation of Sequelae following Treatment - Capone, Rafael Barcelos; Capone, Domenico; Mafort, Thiago; Mogami, Roberto; Rodrigues, Rosana de Souza; Menna Barreto, Miriam; Rufino, Rogerio (Pulmonary Medicine, 2017)
Objectives. To evaluate tomographic changes in pulmonary tuberculosis (TB), degree of agreement among three radiologists regarding tomographic diagnoses, and sequelae following treatment. Methods. Cross-sectional and descriptive study of 74 TB patients confirmed by sputum culture and chest computed tomography before (CT1) and 6 months after (CT2) drug therapy. Results were performed by three radiologists blinded to clinical and laboratory results. Results. Main findings in CT1 included nodules indicating the presence of a tree-in-bud pattern in 93% of cases, ill-defined nodules in 84% of cases, consolidation in 77% of cases, architectural distortion in 71% of cases, cavitary lesions in 62% of cases, and ground glass opacities in 37% of cases. Airway involvement, characterized by increased thickness and dilatation of the bronchial walls, occurred in 93% of cases. Pleural involvement occurred in 54%. There was an agreement on active TB among the three radiologists in 85% of cases. The results in CT2 indicated the presence of architectural distortion in 91% of cases and cylindrical bronchiectasis in 86%. Conclusions. The study established a tomographic pattern for diagnosis of active TB characterized by the presence of airway nodules, consolidation, architectural distortion, and cavitary lesions, and an almost complete degree of agreement (Kappa) was observed among the radiologists (0.85). CT after treatment assists in defining the cure.